The Net Stable Funding Ratio : Impact and Issues for Consideration - Gobat, Jeanne (IMF Working Papers; Working Paper ;, 2014)
As part of Basel III reforms, the NSFR is a new prudential liquidity rule aimed at limiting excess maturity transformation risk in the banking sector and promoting funding stability. The revised package has been issued for public consultation with a plan of making the rule binding in 2018. This paper complements earlier quantitative impact studies by discussing the potential impact of introducing the NSFR based on empirical analysis of end-2012 financial data for over 2000 banks covering 128 countries. The calculations show that a sizeable percentage of the banks in most countries would meet the minimum NSFR prudential requirement at end-2012, and, further, that larger banks tend to be more vulnerable to the introduction of the NSFR. Additionally, by comparing the NSFR to other structural funding mismatch indicators, we find that the NSFR is a relatively consistent regulatory measure for capturing banks' funding risk. Finally, the paper discusses key policy issues for consideration in implementing the NSFR.